Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
y = f(t) = 6t + 50
Step-by-step explanation:
Given:
y = 2x + 50
Where,
x = 3t
Substitute x = 3t into the equation
y = 2x + 50
y = 2(3t) + 50
Open parenthesis
y = 6t + 50
y = f(t) = 6t + 50
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.